Amelioration of Sickle Cell Pain after Parathyroidectomy in Two Patients with Concurrent Hyperparathyroidism: An Interesting Finding - John Muthu; Mir Ali (Case Reports in Medicine)
Patients with sickle cell disease have high morbidity and healthcare utilization due to repeated painful crises. Some coexisting conditions which cause pain similar to sickle cell disease may go undiagnosed in these patients. We report two adults with concurrent hyperparathyroidism who experienced significant improvement in sickle cell pain following parathyroidectomy thereby pointing to hyperparathyroidism as the principal causative factor for their pain. Meticulous evaluation for parathyroid disorders can be rewarding in sickle cell disease.